The Effect of Chronic Renal Failure on the Benzoylecgonine Blood Level: A Case Report. (June 2015) - Guillaud, Daniel A.; Jones, Prentiss; Prahlow, Joseph A.
Abstract : Abstract: Chronic renal failure results in reduced elimination of a variety of substances within the blood, including numerous drugs and their metabolites. This report describes a case of a man who died in jail, after less than 48 hours of being incarcerated, wherein postmortem toxicology testing revealed a blood benzoylecgonine level of 0.25 mg/L with no cocaine detected, suggesting possible recent cocaine use in jail. Autopsy and investigation revealed severe underlying cardiovascular disease and dialysis-dependent CRF, thus accounting for the elevated benzoylecgonine levels and allaying concerns that the man obtained and used cocaine in jail.